THE IMPLEMENTATION OF TRADING PLACE STRATEGY TO IMPROVE THE STUDENTS’ ABILITY IN READING COMPREHENSION OF REPORT TEXT AT EIGHT GRADE OF MTS S. AL-HUSNA MARINDAL MEDAN ACADEMIC YEAR 2018/2019 - Siti Fitri Hasibuan (Universitas Islam Sumatera Utara (UISU), 2018)
The objective of this research is to find out the improvement of the students’ ability in reading the report text by using the trading place strategy. The research was conducted by using Classroom Action Research (Arikunto, 2006). The subject of this study was the nineth grade students in MTs S. AL-Husna, Medan, in academic year 2016/2017. The class consisted of 30 students. The data were taken from the students’ score, observation sheet, diary notes and documentation. Based on the reading tests, the students’ score kept improvement in every test: from pre-test to post test of cycle I and post test of cycle II. The improvement can also be proved by the result of observation sheet and diary notes. Therefore, It was found that teaching reading the report text by implementing the trading place strategy could improve the students’ ability in reading comprehension of the report text.